Efficacy and immunological effects of neoadjuvant chemotherapy with gemcitabine and cisplatin for muscle-invasive bladder cancer - GAO Zhiqiang, CHEN Tao, LIU Lei, SUN Chunshan, JI Yilong, TANG Hao (Zhongguo linchuang yanjiu)
Objective To investigate the efficacy of neoadjuvant chemotherapy with gemcitabine and cisplatin (GC) in patients with muscle-invasive bladder cancer (MIBC), and its impact on immune function. Methods A retrospective analysis was conducted on 65 patients with MIBC who received neoadjuvant chemotherapy at People's Hospital of Zhengzhou. Patients were divided into two groups based on their chemotherapy regimen: 33 cases received gemcitabine and cisplatin (GC group), while 32 cases received methotrexate, vincristine, doxorubicin, and cisplatin (MVAC) (MVAC group). Clinical efficacy, incidence of adverse reactions, and immune function indicators including CD3+, CD4+, CD8+ T lymphocyte percentages, and ratios of CD4+/CD8+, helper T cell (Th)1/Th2, Th17/ regulatory T cell (Treg) were compared between the two groups. Results The treatment efficacy rate in the GC group was 87.88%, significantly higher than that in the MVAC group (65.62%), with a statistically significant difference (χ2=4.532, P＜0.05). No significant difference in the incidence of adverse reactions was observed between the two groups (P＞0.05). After chemotherapy, the GC group had higher levels of CD3+, CD4+ cells, CD4+/CD8+ ratio, Th1, Th17, Th1/Th2, and Th17/Treg compared to the MVAC group, while CD8+ cells, Th2, and Treg levels were lower in the GC group (P＜0.05). Conclusion Neoadjuvant chemotherapy with GC in MIBC patients demonstrates better short-term efficacy and may improve immune function to a certain extent.